2018
DOI: 10.1016/j.carbon.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Raman resonance profile of an individual confined long linear carbon chain

Abstract: This paper reports tip-enhanced, polarization dependent and excitation energy dependent Raman measurements of an individual long linear carbon chain confined in a double-walled carbon nanotube. We determine the band gap of the chain (2.093 eV) from a Raman resonance profile with a line width = 145 meV, which corresponds to a lifetime of ⌧ = 4.5 fs for the excited state of the chain. In the absence of external perturbations, this suggests that the chain's excited state dynamics depend on the confinement inside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 30 publications
2
47
0
Order By: Relevance
“…It turns out that such systems are already in the focus of intensive scientific research because of their exceptional properties. Let us mention just a few: carbyne, a material stronger than graphene, Kagome lattices, interesting for their exotic topological states, and copper‐oxide planes relevant for high‐temperature superconductivity.…”
Section: Discussionmentioning
confidence: 99%
“…It turns out that such systems are already in the focus of intensive scientific research because of their exceptional properties. Let us mention just a few: carbyne, a material stronger than graphene, Kagome lattices, interesting for their exotic topological states, and copper‐oxide planes relevant for high‐temperature superconductivity.…”
Section: Discussionmentioning
confidence: 99%
“…1.8 and 2.25 eV), as verified by wavelength-dependent Raman spectroscopy in an ensemble sample containing many different DWCNT chiralities and thus distinct C-mode frequencies (Figure 7c) [117] as well as on the single tube/single chain level (Figure 7d). [119] These experiments revealed that the SWCNT inner diameter could be an additional handle to tune the optical and vibrational properties of the encapsulated chains, while also largely affecting LCC synthesis yield. So far the filling ratio has not yet been determined accurately, but given the extremely high Raman cross-section reported of encapsulated LCCs, [118] and comparing the Raman signals of the LCCs with those of the surrounding CNTs, most likely the filling fraction is rather low.…”
Section: Synthesis Of Linear Carbon Chains Inside Swcntsmentioning
confidence: 97%
“…d) Raman excitation profile of an individual encapsulated chain which can be measured due to the extremely high Raman cross-section of the encapsulated chains. Reproduced with permission [119]. Copyright 2018, Elsevier.…”
mentioning
confidence: 99%
“…Carbyne has attracted significant interest due to its anticipated outstanding mechanical 15 , thermal 16 , and electronic 17 properties. In particular, carbyne possesses a band gap that is sensitive to external perturbations [18][19][20][21][22] and can possibly be switched externally from a semiconducting to a metallic state 23,24 , which points out the potential of carbyne for nanoelectronic devices. While the synthesis of carbyne has long been challenging [25][26][27] , large progress has been made in recent years using carbon nanotubes as nanoreactors and protective nanocontainers [28][29][30][31][32][33][34][35] , as illustrated in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%
“…While the synthesis of carbyne has long been challenging [25][26][27] , large progress has been made in recent years using carbon nanotubes as nanoreactors and protective nanocontainers [28][29][30][31][32][33][34][35] , as illustrated in Figure 1a. Raman studies have played an important role in the investigation of carbyne, but have so far been restricted to Stokes scattering [18][19][20]29,31 . Extending this scope to the anti-Stokes side of the spectrum is not only of practical relevance for sideband thermometry, but can aid in assessing fundamental material properties such as phonon lifetimes 36 and optical transition energies 37 , as well as extending the mechanistic understanding of the Raman process 8 .…”
Section: Introductionmentioning
confidence: 99%